2015
DOI: 10.1074/jbc.m115.649210
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides Promote S-Nitrosylation and Proteasomal Degradation of Liver Kinase B1 (LKB1) in Macrophages in Vivo

Abstract: Background: LKB1 is an important serine/threonine kinase with key roles in cancer and metabolism. How LKB1 is regulated remains unclear. Results: LPS induced S-nitrosylation of LKB1, resulting in its proteasomal degradation, which aggravated LPS-induced mortality in mice in vivo. Conclusion: LPS induces LKB1 degradation through S-nitrosylation in macrophages.Significance: We have unveiled a novel mechanism for regulating LKB1 stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…OxLDL is known to induce iNOS expression in macrophages 28, 29 , and we had previously found that NO-mediated s-nitrosylation could promote LKB1 degradation 30 . Thus, we first tested if OxLDL differentially induces iNOS expression in macrophages versus vascular smooth muscle cells.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…OxLDL is known to induce iNOS expression in macrophages 28, 29 , and we had previously found that NO-mediated s-nitrosylation could promote LKB1 degradation 30 . Thus, we first tested if OxLDL differentially induces iNOS expression in macrophages versus vascular smooth muscle cells.…”
Section: Resultsmentioning
confidence: 97%
“…We found that OxLDL can robustly induce iNOS expression in macrophages, which is consistent with a previous report 29 , however, we cannot detect iNOS expression in VSMCs after OxLDL exposure (Supplemental Fig 2). We have previously found that NO-mediated s-nitrosylation promotes LKB1 degradation 30 . It is thus possible that OxLDL-induced iNOS expression in macrophages may promote LKB1 degradation through s-nitrosylation, whereas VSMCs, which lack iNOS expression, undergo no such effect.…”
Section: Discussionmentioning
confidence: 99%
“…NO-stimulated protein degradation occurs for several non-P450 proteins, such as iron regulatory protein 2 (IRP2) [33], insulin receptor substrate (IRS) -1 and -2 proteins [34][35], mouse double minute 2 homolog (Mdm2) [36], O 6 -alkylguanine-DNA alkyltransferase [37], serine/threonine-protein kinase STK11 [38], cyclin-dependent kinase 5 [39], and caspase 8 inhibitory protein [40]. In the case of IRP2, opposite effects have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces degradation of programmed cell death protein 4 (PDCD4) in a mammalian target of rapamycin signaling–dependent manner, which leads to an increased IL‐10 level (44). Liu et al (45) demonstrated that LPS accelerates liver kinase B1 decay by S‐nitrosylation–dependent proteasome pathways. Our results support the transcriptional control of Nrp1 by LPS in macrophages.…”
Section: Discussionmentioning
confidence: 99%